Innovative Sport Consumption Experience: An Empirical Test in Spectator and Participant Sports - Masayuki Yoshida; Makoto Nakazawa (Journal of Applied Sports Management, 2016)
Understanding what aspects of sport consumption experiences are necessary to be innovative to gain and sustain long-term competitive advantage is a key issue in sport marketing. Presented herein is a multi-dimensional conceptualization of innovative sport consumption experiences, including six dimensions: sport performance, aesthetic environment, facility convenience, online services, brand community, and loyalty programs. Data were collected from spectators at a professional baseball game and users of a running station in Japan. Through a confirmatory factor analysis (CFA) and structural equation modeling (SEM), we assessed the construct and nomological validity of the proposed scale to measure the innovative sport consumption experience. In both settings, aesthetic environment innovativeness was the dominant factor in enhancing consumer satisfaction and brand attitude. Furthermore, the effects of brand community innovativeness on consumer satisfaction, brand attitude, and behavioral intentions were positive and significant for the baseball sample, while online services innovativeness positively influenced consumer satisfaction and brand attitude in the running station setting. The proposed framework was a useful model for understanding consumers' assessments of innovative sport consumption experiences based on specific innovation points.
Keywords: innovative sport consumption; product innovativeness; service innovation; experience innovation; consumer loyalty